Decentralized robust mixed H2/H∞ reactive power control of DFIG cluster using SMES. (December 2019) - Islam, Kazi Shariful; Seyedmahmoudian, Mehdi; Stojcevski, Alex
Highlights: Proposed controller can significantly enhance the transient and voltage stability of DFIG-based power system. Proposed controller successfully tackles uncertainties and withstand operating condition variation. Proposed controller delivers superior transient performance over conventional PI-based SMES controller. Abstract: This paper proposes a method for developing a decentralized robust mixed H 2 / H ∞ output feedback reactive power control using superconducting magnetic energy storage (SMES) which improves transient stability of the DFIG cluster. The decentralized mixed H 2 / H ∞ output feedback optimal control design provides robustness via optimization of the worst-case quadratic performance of the underlying uncertain cluster system and guarantees that the obtained controller is a locally optimal or on the boundary of the H ∞ norm constraint. The proposed controller takes into account the uncertainty of model parameters, which have a significant effect on the stability of the critical modes, which are identified from the critical parameter analysis. The proposed controller also tackles local uncertainties as well as interconnection effects of decentralized systems. The iterative optimization method to synthesize the controller and the steps involved in the controller design for the test system are presented. The performance of the proposed SMES controller is evaluated and the superiority of the designed control method over the conventional PI-based SMES controller is demonstrated.